Modelling and dynamic simulation of a hybrid liquid desiccant system regenerated with solar energy - Coca-Ortegón, Adriana; Prieto, Juan; Coronas, Alberto (Elsevier, 2016)
The combination of liquid desiccant systems with conventional vapour compression chillers, usually known as hybrid liquid desiccant systems (HLDS), is a promising alternative when temperature and humidity need to be controlled in air conditioning applications. One of the advantages of this technology is that different kinds of energy can be integrated, particularly low temperature solar thermal energy, which can reduce the electrical consumption of the system. These kinds of systems are typically analysed by discrete steady-state simulations, which show how the system behaves in design conditions. However, dynamic simulations can provide information about the seasonal performance and help to set an appropriate control strategy. This paper describes the modelling and dynamic simulation of an HLDS using Trnsys. Because there are non-standard components for the main elements of a liquid desiccant subsystem (LDS), an alternative modelling method based on performance tables has been developed. The simulation is carried out for Kuala Lumpur, a city with high humidity and ambient temperatures, where air conditioning is required throughout the year. The control strategy is also defined. Finally a sensitivity analysis is performed for the case analysed.
Keywords: Desecantes; Energía solar; Dehumidification; Air conditioning; Hybrid liquid desiccant system; Solar energy